2022
DOI: 10.1007/s10796-022-10286-1
|View full text |Cite|
|
Sign up to set email alerts
|

Authenticity in Objects and Activities: Determinants of Satisfaction with Virtual Reality Experiences of Heritage and Non-Heritage Tourism Sites

Abstract: Virtual Reality (VR) is becoming an increasingly important technology in a host of industries, including tourism. VR can provide virtual experiences before, during, or in lieu of real-world visits to tourism sites. Hence, providing authentic experiences is essential to satisfy guests with the site and technology. This study analyzes survey data using PLS to identify the determinants of satisfaction with non-immersive VR experiences of heritage and non-heritage tourism sites. Results from 193 subjects reveal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 78 publications
(208 reference statements)
2
7
0
Order By: Relevance
“…The study found that higher levels of user satisfaction were associated with a greater sense of presence, which can improve the integration between the user and the virtual experience. Nam et al (2023) found that higher levels of user satisfaction were associated with authentic experiences which are essential to satisfy guests with the site and technology. greater immersion, suggesting that satisfaction can improve the user's ability to integrate with the virtual environment and suspend disbelief.…”
Section: Findings Through the Analysis Ofmentioning
confidence: 98%
“…The study found that higher levels of user satisfaction were associated with a greater sense of presence, which can improve the integration between the user and the virtual experience. Nam et al (2023) found that higher levels of user satisfaction were associated with authentic experiences which are essential to satisfy guests with the site and technology. greater immersion, suggesting that satisfaction can improve the user's ability to integrate with the virtual environment and suspend disbelief.…”
Section: Findings Through the Analysis Ofmentioning
confidence: 98%
“…The Zhou et al (2020) study pointed out that when tourists want to seek help through word of mouth, the authenticity of information on social media platforms can help them solve problems more effectively. In terms of authenticity research, Nam et al's (2023) study went through two groups of VR-presented attractions: One group was VR-presented heritage destinations, while the other group was VR-presented non-heritage destinations. Their study found that only in VR-presented heritage destinations based on VR presentation did tourist's authenticity positively predict satisfaction.…”
Section: Perceived Authenticity In Digital Tourismmentioning
confidence: 99%
“…However, to some extent, we reduced such biases by searching all the major databases and following the steps indicated by Kitchenham and Charters (2007) and Dybå and Dingsøyr (2008). In addition, we only included articles that use the keyword metaverse, indicating that other relevant articles may exist which were not part of our analysis, such as articles on virtual worlds that do not mention metaverses (e.g., Nam et al, 2022;Zhang et al, 2020). To remedy this limitation, we conducted a backward-forward search (Webster & Watson, 2002) to manually identify potentially relevant articles.…”
Section: Limitationsmentioning
confidence: 99%